Witches of East End - De la Cruz, Melissa, 1971- (New York : Hyperion, 2011)
Freya Beauchamp, a 19-year-old bartender engaged to a Hamptons society beau but in love with his brother; her sister, Ingrid, a single librarian; and their mother, Joanna Beauchamp, are all witches living together in relative harmony, as they have for several centuries. They have significant powersraising the dead, flyingall of which they have been forbidden to use by the White Council after a debacle in 17th-century Massachusetts. As compensation they have gained immortality, but as the story opens, the restrictions placed on them have begun to fray, and they are all "leaking" magic, prompting them to rebel and live true to their natures. The citizens of East End find themselves cured of writer's block, infertility, and skin infections, and generally profiting from the benevolent attentions of the Beauchamps. Then small disturbances become large ones, otherworldly creatures show up, and humans disappear.
Keywords: Witches -- Fiction; Good and evil -- Fiction; Occult fiction